Management of Athletes with Postconcussion Syndrome - Diaz, Deborah S. (Seminars in Speech and Language, 2014)
Rehabilitation for athletes with postconcussion syndrome requires emphasis on both cognitive and physical rest with a gradual return to activity and sports. As the athlete becomes more active, the rehabilitation and sport professional should pay close attention to symptoms of concussion, like headache, dizziness, nausea, and difficulty concentrating. The Zurich Consensus Statement on Concussion in Sport provides a systematic approach to increasing the intensity of physical activity while attending to postconcussion symptoms. During the incident that led to a concussion, the injured athlete may have incurred injuries to the vestibular and balance system, which are not directly related to concussion. These conditions are best addressed by professionals with specific training in vestibular rehabilitation, most commonly physical therapists. Benign paroxysmal positional vertigo is a condition in which otoconia particles in the inner ear dislodge into the semicircular canals, resulting in severe vertigo and imbalance. This condition frequently resolves with a few sessions with a vestibular therapist and a home exercise program. In conditions like gaze instability, motion sensitivity, impaired postural control, and cervicogenic dizziness, improvement is more gradual and requires longer follow-up with a physical therapist. In all of these conditions, it is important to consider that the patient with postconcussion syndrome will likely recover more slowly than others and should be monitored for symptoms of postconcussion syndrome throughout intervention.
Keywords: Postconcussion syndrome; treatment; vertigo; dizziness; postural instability; gaze stability; benign paroxysmal positional vertigo; cervicogenic dizziness; graduated exertion